Redefining Classroom Engagement through Gamified Sociocollaborative Learning for Future Ready Education - Suardi Suardi (PT FORMOSA CENDEKIA GLOBAL, 2026)
Student engagement in junior high school, particularly among Grades VII and VIII students, remains limited due to conventional teaching practices. This study examines the effectiveness of gamified sociocollaborative learning in enhancing cognitive, affective, and behavioral engagement. Using a mixed-methods sequential explanatory design, qualitative data from interviews and observations informed a quantitative survey of 72 students in Pasaman Regency. Thematic and regression analyses show that integrating gamification elements with collaborative activities significantly increases student motivation, interaction, and active learning, with the strongest impact on cognitive engagement. The study concludes that gamified sociocollaborative learning is an effective and innovative approach to improving student engagement at the junior high school level.